KEAWETAN BATANG AREN (Arenga pinnata Merr.) - Ginuk Sumarni; Agus Ismanto; Mohammad Muslich (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Aren (Arenga pinnata Merr ) is one of the natural resources of the tropics which has been used widely in the daily life of the local community as a sustainable resource due to its wide distribution, high availability, and desirable properties. The significant uses in Indonesia are for building material, making various baskets, roof, sugar, candied fruits, and handicraft.The specimen of aren was selected from Jasinga, West Java. A log sample was taken from three height levels of the stem, viz top, middle and bottom sections. Each section was tested to the dry wood termite Cryptotcrmes cynoccphalus Light., the subterranean termite Coptotcrmes curvignathus, Holmgren the powder post beetle and Heterobostrychus aequalis Wat the fungi Schyzophyllum commune Fr., Pycnoporus sanguincus (Fr.) Karst, and the Dacryopinax spathularia (Schw.) MarstThe results showed that aren stem specimens taken from the top, middle and bottom sections are resistant to dry wood termite (Cryptotcrmes cynocephalus Light.), especially the bottom section which can be classified as durability class I. The results also showed that aren stem is resistant to powder post beetle (Heterobostrychus aequalis Wat.) and fungi (Schyzophyllum commune Fr., Pycnoporus sanguincus (Fr.) Karst. and Dacryopinax spathularia (Schw.) Marst.). On the other hand, aren stem is not resistant to the subterranean termite Coptotermes curvignathus Holmgren, especially the top section which can be classified as durability class V.